Identification of unique proteins in vitreous fluid of patients with noninfectious uveitis. Issue 8 (26th August 2018) - Kasudhan, Kripa Shanker; Sarkar, Subendu; Gupta, Vishali; Gupta, Amod; Chakraborti, Anuradha
Abstract: Purpose: Uveitis is a cause for concern in the developing countries like India. Its poor diagnosis and lack of proper therapeutics often cause blindness in children and young adults. Moreover, the exact mechanism of pathogenesis of different types of uveitis is still elusive. Modern proteomic techniques are found to be advantageous for an in‐depth understanding of the ocular physiology using proteomic diversity. Our aim was to identify unique proteins involved in the pathogenesis of autoimmune or noninfectious uveitis. Methods: Vitreous fluid samples ( n = 90) were obtained from infectious ( N = 34) and noninfectious ( N = 56) uveitis patients, and their protein profiles were compared by analysing sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS‐PAGE) and 2D electrophoresis. Unique proteins were identified through matrix‐assisted laser desorption ionization–time‐of‐flight mass spectrometry (MALDI‐TOF MS) and further studied for pathway analysis. Results: Protein spots having different molecular weights were observed in noninfectious vitreous fluid samples. Enzymatic digestion of these spots after MALDI‐TOF MS analysis revealed different proteins. We identified 25 different proteins through SDS‐PAGE and 22 through 2D electrophoresis. 50% of the proteins from SDS‐PAGE were associated with heterotrimeric G‐protein signalling pathway–rod outer segment phototransduction. 50% proteins from SDS‐PAGE and 20% from 2D electrophoresis revealed association with de novo purine biosynthesis. Carbonic anhydrase 1 and serpin B3 were found to be common in both analyses. Conclusion: High‐throughput proteomic and pathway analyses have exposed the potential association of these proteins with autoimmune pathogenesis in uveitis. The exact role of most of the proteins in autoimmune uveitis is yet to be unfurled.